Pemanfaatan Wilayah Yang Tidak Sesuai Rencana Tata Ruang Wilayah Atas Rencana Pembangunan Pabrik Tapioka - Susanti Susanti; Slamet Riyanto (Simbur Cahaya, 2025)
The spatial planning of the North Lampung district is about to undergo an overhaul due to the planned construction of a tapioca factory by PT Sinar Baru Rusa Prima in the Abung Kunang area, which is not an industrial area in accordance with the established Regional Spatial Plan. This became a polemic because the North Lampung Regency legislature had submitted a recommendation letter to stop the construction of the tapioca factory because it was not in accordance with the RTRW. However, this is constrained because the North Lampung Regency Government has obtained a Space Utilization Conformity Permit so that the tapioca factory construction plan will continue by amending the North Lampung Regional Regulation Number 4 of 2014 concerning the North Lampung Regency Spatial Plan 2014-2034 which previously had five industrial areas to thirteen industrial areas.This research uses a normative method using literature study. The purpose of this research is to analyze the impact of the plan to build a tapioca factory by PT Sinar Baru Rusa Prima in the Abung Kunang area, North Lampung Regency, on the established regional spatial planning. This research aims to identify the discrepancies between the factory development plan and the applicable Regional Spatial Plan, and evaluate the implications of these changes for regional development.